2010
DOI: 10.1152/ajprenal.00450.2009
|View full text |Cite
|
Sign up to set email alerts
|

Renal salt wasting and chronic dehydration in claudin-7-deficient mice

Abstract: Claudin-7, a member of the claudin family, is highly expressed in distal nephrons of kidneys and has been reported to be involved in the regulation of paracellular Cl(-) permeability in cell cultures. To investigate the role of claudin-7 in vivo, we generated claudin-7 knockout mice (Cln7(-/-)) by the gene-targeting deletion method. Here we report that Cln7(-/-) mice were born viable, but died within 12 days after birth. Cln7(-/-) mice showed severe salt wasting, chronic dehydration, and growth retardation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 41 publications
(39 reference statements)
4
80
0
1
Order By: Relevance
“…CLDN7 KD resulted in a 30% decrease in TER but no significant change in ion selectivity (P Cl /P Na ; siRNA 772 shown as representative; Table 1), indicating a TJ barrier-function defect. This is consistent with the in vivo findings that CLDN7 KO animal kidneys lose major extracellular ions, such as Na + , K + , and Cl -, in a similar rate (14). Our findings suggest that the paracellular Clchannel in the collecting duct is formed by CLDN4 and CLDN8, without involving CLDN3 or CLDN7.…”
Section: Mutagenesis Identifies a Locus Of Amino Acids Critical For Csupporting
confidence: 92%
See 2 more Smart Citations
“…CLDN7 KD resulted in a 30% decrease in TER but no significant change in ion selectivity (P Cl /P Na ; siRNA 772 shown as representative; Table 1), indicating a TJ barrier-function defect. This is consistent with the in vivo findings that CLDN7 KO animal kidneys lose major extracellular ions, such as Na + , K + , and Cl -, in a similar rate (14). Our findings suggest that the paracellular Clchannel in the collecting duct is formed by CLDN4 and CLDN8, without involving CLDN3 or CLDN7.…”
Section: Mutagenesis Identifies a Locus Of Amino Acids Critical For Csupporting
confidence: 92%
“…Thus, CLDN8 is required for the paracellular Cl -channel in the collecting duct. Immunofluorescence analyses have shown that CLDN3 and 7 are also expressed in the collecting ducts of mouse and rat kidneys (12,14), although one study described CLDN7 in the collecting ducts as located primarily on the basolateral membrane (13). Both M-1 and mIMCD3 cells express endogenous CLDN3 and CLDN7.…”
Section: Mutagenesis Identifies a Locus Of Amino Acids Critical For Cmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Mice with constitutive knockout of claudin-7 die in neonatal life of renal salt wasting, dehydration, and renal failure, consistent with a role for claudin-7 in ASDN Cl 2 reabsorption. 86 Claudin-4 and -8 act as cation barriers when overexpressed MDCK cells. [87][88][89] However, knockdown experiments in M1 and IMCD3 cell lines suggest that in native collecting ducts they are more likely to function primarily as Cl 2 pores.…”
Section: Role Of Claudins In the Aldosterone-sensitive Distal Nephronmentioning
confidence: 99%
“…Crosses were established between Cldn7 C/¡ breeders 14 and kidneys from the newborn pup offspring were sectioned for histology and total nephron number assessment. Kidney sections from all of the pups including the homozygous and heterozygous mutants appeared grossly normal with no defects noted in the extent of ureteric bud branching morphogenesis or in the organization of the cortex and the medulla.…”
Section: Multiple Claudins Are Expressed During Mouse Kidney Developmentmentioning
confidence: 99%